Strategies to Teaching Speaking Online: A Case Study at University of Halu Oleo Kendari - Eva Gultom (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Since the Covid-19 pandemic globally widespread, education has gradually transformed into more digitalized. Schools and educators are forced to be more eligible in using technology and online devices. This study will examine the effectiveness of the online platform used to teach speaking and the teaching speaking comparison between online and face-to-face classrooms. In collecting the data, the live online class observation was conducted to identify the strategies of teaching speaking. At the end of this study, the writer found that either online or face-to-face meeting has positive and negative impacts on teaching speaking English. Keywords: teaching speaking online, strategy, English, technology, digital